Parent’s Positive Relations with Children’s Activity is Condition of Primary School Pupil’s Humanity - Bakutytė, Rima (Acta Paedagogica Vilnensia, 2002)
The aim of this article is to disclose connection between parent’s positive relations with pupils’ activity and their II-IV grade children’s humanity based on research data. In the course of diagnostic research 331 pupils from Šiauliai, Vilnius, Šventoji schools (168 girls and 163 boys; 112 second formers, 107 third formers, 112 fourth formers), their 18 teachers and 309 parents were studied. The results of factorial and correlative analysis states that the essential features of the relationship of the II-IV formers’ parents with their children’s activities are the encouragement to work independently, attention to the results of children ’s activities, help when performing tasks, efforts to give a chance of studying at home and elsewhere. In the course of research it was sought to establish real and ideal (imaginary) parents’ relationship with their children’s activity. It was ascertained that the attitude of boys’ and girls’ senior and junior primary school pupil’s parents towards the activity of their children was positive enough (with a few exceptions). But real parents’ relationship with children’s activity was not very positive. It was found that 26,3% of them did not give real chances for their children to use books, reference books, other facilities, did not encourage their going to libraries etc. There are even such parents who are not interested in children’s activities, do not help them, do not encourage their independent work, do not notice the results of their activities (from 4,3% to 7,6%). It was also revealed that children’s humanity depends a lot on the development of parents’ relationship with their children’s activities. But this dependence seems to be not direct. Children’s activities are made on sensitive, sincere, responsible and a little dignified child’s behaviour with parents, teachers and classmates (from c2 = 20,7, p < 0,01 to c2 = 61,5, p < 0,0001). Besides parents’ relationship with children’s activity determines better insight into the contents of straightforwardness and indulgence (0,22, r = 0,21 ), more favourable was attitude towards sincerity, sympathy (r = 0,20 r = 0,21 ). Consequently, parents’ relationship with children’s activity determines a lot not only their self-realization, but the expression of humaneness on cognitive and behavioural level too.